The double-edged sword of digital self-care: Physician perspectives from Northern Germany - Fiske, Amelia; Buyx, Alena; Prainsack, Barbara (Social Science & Medicine, 2020)
Increasingly, patients are expected to take initiative and care for themselves through practices of digital self-care: by generating data, by looking for people who can help them make sense of the information, and by being the main actors in disease prevention. Equipped with smart phones and other tools to collect data on various aspects of their bodies and lives from brain waves to activity to diet, patients are expected to prevent lifestyle diseases and diagnose their own medical problems, heralding an entirely new model of care within doctor-patient relationships. In this article we explore physician perspectives on how digital self-care practices are encountered, understood, and incorporated (or not) in the health care system. We carried out in-depth, semi-structured interviews with 15 doctors in Northern Germany in 2018 in order to explore how they included digital data in clinical decisions, how they understood practices of digital self-care, and how they saw these practices affect doctor-patient relationships. Our findings indicate notable frictions between narratives of ‘e-patients’ and digitally-empowered people in public media and scholarly literature on the one hand, and what doctors reportedly experience in their own practice on the other. We conclude that tech-forward ideas surrounding lay practices of medical emancipation do not ‘travel lightly’ across different contexts, but are taken up unevenly in and outside of the clinic. Moreover, the personal relationships through which digital self-care practices are undertaken remain central to the meaningful and safe application of new technologies and applications – something that often escapes debates over patient empowerment and digital technology.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Datafication of health; Digital self-care; Doctor-patient relationship; Germany; Participation; Patient empowerment